Patients’ Knowledge of Artemisinin-Based Combination Therapy Treatment and Its Impact on Patient Adherence - Agani Afaya; Solomon Mohammed Salia; Peter Adatara; Richard Adongo Afaya; Solomon Suglo; Milipaak Japiong (Journal of Tropical Medicine)
Despite increased support from government and other stakeholders for malaria control over the past decade, malaria burden remains high in many endemic countries, particularly in Sub-Saharan Africa. This study aimed to assess patients’ knowledge of antimalarial treatment (ACT) and its association with patient adherence. A descriptive cross-sectional study design was employed in this study. Data were collected from April to May 2017. Both descriptive and inferential statistics in the form of frequencies, percentages, mean values, standard deviations, and Pearson’s chi-square test were generated by use of Microsoft excel spreadsheet and IBM Statistical Package for Social Sciences (SPSS) version 23. The average age of the respondents surveyed for this study was 42.27 ± 11.09. Adherence level to ACT was 47%. The results showed that there was a significant association between respondents’ knowledge of the efficacy of antimalarial medication (p = 0.003), benefits of completing antimalarial treatment course (p = 0.001), and consequences of not completing the doses of antimalarial medication prescribed (p = 0.002) and adherence to ACT. This study then recommends that improving patients’ knowledge regarding the efficacy, benefits of completing ACT, and consequences of not completing ACT treatment may improve the likelihood of patients adhering fully to ACT.